Edukasi Jenis Penyakit pada Musim Hujan untuk Menciptakan Kesehatan Masyarakat di RSCS Kekandhangan Banyuraden Gamping Sleman - Agustin, Roviana Nurda; Nirwana, Astika Candra (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Disease awareness is a challenge for the community. Education through community service needs to be developed by involving and empowering the community to increase their knowledge of several types of diseases that can occur during the rainy season. This includes conducting ongoing education to increase public knowledge and foster a high level of health awareness, thus preventing disease. The purpose of this community service activity is to be aware of diseases during the rainy season to create public health at RSCS Kekandhangan Banyuraden Gamping Sleman so that it can increase public awareness to improve health and early prevention of diseases. This community service activity was carried out on Sunday, October 5, 2025 at 15.00-18.00 WIB by 2 lecturer speakers attended by 30 people who were carried out well overall according to the plan that had been prepared. The success of this activity was an increase in public understanding of diseases during the rainy season through the results of the pretest and posttest assessment. The implementation of this activity is expected to be carried out continuously, sustainably and developed in collaboration with existing activities in the village so that public health can be monitored and equip residents with awareness and responsibility for their own health so that they can achieve an increase in public health.